Penentuan Kadar dan Distribusi Spasial Logam Berat Kadmium (Cd) pada Rumput Laut Euchema cottonii Asal Perairan Kab. Takalar dengan Metode Spektrofotometer Serapan Atom (SSA) - Muh. Tasjiddin Teheni; Syamsidar HS (Study Program of Chemistry - Alauddin State Islamic University of Makassar, 2013)
Seaweed is one of the potential export commodity to be developed in Indonesia. Types of seaweed in Indonesia that have high economic value, namely Eucheuma cottonni where Takalar is one seaweed production center in South Sulawesi. This study aimed to determine the levels of heavy metal cadmium in seawater and seaweed and the distribution of heavy metals in the waters of Takalar. The cadmium quality kwelswere determined by Atomic Absorption spectrophotometry (AAS) method. The sample analysis did through the process of destruction used HNO3, 10% HCl. The total spots of sampling are six in ekuding Sanrobone, Maciini Baji, Batiro Baji, Laikang and Puntondo village were spreaded out from North to South. The results of research shaowed that Cd metal was distributed at six site where the highest level was on Sanrobone village that was 0.4725 ppm and the lowest in Puntondo village that was 0.3910 ppm. The high levels of cadmium was influenced by levels of Cd on the sea water where the highest level of Cadmium were in the Sanrobone village and the lowest level in the Puntondo village. The levels of Cadmium metal on sea and Euchema cottonii seaweed at six has exceded the threshold set by PP RI No.20/1990 was 0,1 ppm.